Dificuldades e concepções de alunos de um curso de licenciatura em matemática, sobre derivada e suas aplicações - Ramos, Vagner Valeiro (2009)
This is a diagnostic research, whose objective is investigate the students' knowledge that already passed a Calculus course derivative , as much as its applications and try to classify the difficulties of these students before these activities.We elaboreted then a test composite of four tasks, that deal with the theme. This test was structured according to Raymond Duval's theory - Register of Representation Semiotic. With the data got we carried out the analyses qualitatively and quantitatively. We explored in the test the algebraic and graphic representations of a function and of its derivative and the relation that there are between them, that well demand conversions to be obtained, well demand treatment. After the analyses of the results, we observed that the students manipulate well the algebric representations, but many of the students neither get to indentify the need procedures, nor do use of the concept of derivative, for a resolution of a determineted situation of aplication